Floating Goat - Gaydos, Nora (Nigeria, 2001)
The goat. The goat in a robe. The goat in a robe is floating home. The goat in a robe is floating home on a boat. The goat in a robe is floating home on a boat with holes. Oh, no! This boat won't float. The goat woke up. The goat holds onto a rope. The soaking goat drove hom on the road...
Keywords: Animal Adventure; Juvenile Fiction